Pengaruh Tingkat Status Sosial Ekonomi terhadap Pemahaman Pemilu Pemilih Pemula pada Pilpres 2024 di Desa Suka Mulia Kecamatan Secanggang Kabupaten Langkat - Sellia Rahmawati; Halking Halking (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2024)
The Presidential Election (Pilpres) is one of the most important moments at the national level where all people are involved. Candidates who participate in the presidential election cannot be separated from the image and support of the parties that form their political consciousness. Usually, a party or coalition of parties supports a pair of candidates for President and Vice President. Parties are not only a forum for expressing political views but also as guardians of responses to the aspirations of members and society. Openness and good performance from a party can make people like it, and even make them loyal voters. This research aims to determine whether there is an influence of socio-economic status level on the electoral understanding of first-time voters in the 2024 presidential election in Suka Mulia Village, Secanggang District, Langkat Regency. The type of research used in this research is quantitative research with a survey approach. Data collection was carried out through primary and secondary data. The results of the validity test for the two variables, namely variable From the results of calculating the t count of 5.0 and t table of 0.00657, it can be seen that the t count is greater than the t table, namely 5.0 > 0.00657, so Ho is rejected and this means that there is a significant influence of the level of socio-economic status on understanding elections. beginner voters in the 2024 presidential election in Suka Mulia Village, Secanggang District, Langkat Regency.